Cigarette Smoking in Pregnancy: Its Influence on Birth Weight and Perinatal Mortality. Issue 5806 (15th April 1972) - Butler, N. R.; Goldstein, H.; Ross, E. M.
Abstract : In a British population cigarette smoking during pregnancy increased the late fetal plus neonatal mortality rate by 28% and reduced birth weight by 170 g, and these differences persist even after allowing for a number of "mediating" maternal and social variables. A change in smoking habit by the end of the fourth month of pregnancy places a mother in the risk category appropriate to her changed habit. This evidence should have important implications for health education aimed at getting pregnant mothers to give up smoking.